IgA Nephropathy in Czech Patients - Are We Able Reliably Predict the Outcome? - Dita Maixnerova; Michaela Neprasova; Jelena Skibova; Jana Mokrisova; Romana Rysava; Jana Reiterova; Eva Jancova; Miroslav Merta; Josef Zadrazil; Eva Honsova; Vladimir Tesar (Karger Publishers, 2014)
Background/Aims: The aim of our study was to retrospectively analyse data of 520 Czech patients with IgA nephropathy (IgAN) and to specify the risk factors affecting renal survival of IgAN patients. Methods: Cox proportional hazards regression model was used to evaluate the effects of different variables on renal survival during a median follow up of six years. McNemar´s test was used to analyse the progression of renal function according to Bartosik´s formula. Results: In our retrospective analysis of 520 Czech IgAN patients Cox proportional hazards regression model with five variables [hypertension, sex, GFR, proteinuria, age] was used. Significant regression coefficient was found for GFR, hypertension and proteinuria. Using stepwise algorithm GFR (OR = 3.09), hypertension (OR = 2.09) and proteinuria (OR = 1.97) were found as the most important factors for renal survival in our group of IgAN patients. Among patients with CKD 3 we found significantly better renal survival in patients with proteinuria Conclusion: Our retrospective study of 520 Czech IgAN patients confirmed GFR, hypertension and proteinuria as the most important factors affecting the prognosis of IgAN patients. We validated Toronto Bartosik´s formula to predict prognosis of IgAN patients.